PERAN FAKTOR PSIKOSOSIAL TERHADAP PRESTASI AKADEMIK PADA MAHASISWA - , MAHARGYANTARI PURWANI DEWI,S.PSI.,M.SI. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to examine the role of psychosocial factors on student academic achievement. Subject in this study consist 368 college students. The instrument for four variables using scale such as parental support, interest in extracurricular, academic self-efficacy, motivation to learn and Academic Performance Index (CPI) to determine student academic achievement. The analysis used in this study was path analysis. The first results indicate the model influence parental support on academic achievement and have goodness of fit. Second, parental support was not direct effect to academic achievement. Third, social support indicated that there was indirect effect to academic achievement mediated interest in extracurricular. Fourth, social support indicated that there was indirect effect to academic achievement mediated academic self-efficacy. Fifth, social support indicated that there was no indirect effect to academic achievement mediated motivation to learn. Keywords: academic achievement, parental support, interest in extracurricular, academic self efficacy, motivation to learn.